Ses dekades Ou Testament-teologie (1952–2012): Van één Spreker tot verskeie menslike sprekers - Spangenberg, Izak J. J. (HTS teologiese studies, 2012)
Six decades of Old Testament theology (1952–2012): From hearing only One Voice to hearing many human voices. This article took a look at what has transpired in the field of Old Testament theology during the past six decades. The year 1952 saw the publication of G. Ernest Wright’s book God Who Acts: Biblical Theology as Recital which is regarded as reflecting a new approach to Old Testament theology. However, the years 1970 and 1989 were also deemed to be important years in the study of the Old Testament, reflecting major changes. The six decades were thus divided into three periods (1) 1952–1970, (2) 1970–1989, and (3) 1989–2012. It was argued that the theologies which were published during the respective periods share a few common trends. This article identified and reflected on these. At the beginning of the six decades revelation through history was an important conviction and impacted on the theologies of the first period. Literary and religious studies during the seventies and nineties of the previous century had little impact on the theologies of the second and third periods. However, during the third period an Old Testament theology which set a new trend, saw the light. This theology has the title Theologies in the Old Testament and reflected a shift from hearing only One Voice in the Old Testament to hearing many human voices.